CHILDREN’S RIGHTS IN THE CROSSFIRE: EXAMINING INDONESIA'S DIVORCE LEGAL CULTURE - Sri Ciptorukmi, Anjar; Safira Rahma, Adalia (LITIGASI, 2024)
The divorce rate in Indonesia has shown a significant annual increase, rising from 20.24% in 2018 to 29.39% in 2023, with an average growth of approximately 2% per year. This study examines the legal culture surrounding divorce in Indonesian courts and explores the potential for law to transform societal attitudes and practices. Using a qualitative descriptive approach, the research relies on secondary data, including court decisions, prior studies, and relevant legislation, analyzed through interactive methods. The findings reveal five key aspects of Indonesian legal culture related to divorce: (1) most divorce filings are initiated by wives; (2) divorces frequently occur during the early years of marriage; (3) child rights are often overlooked in divorce lawsuits; (4) many cases proceed without the defendant’s presence; and (5) societal norms tend to tolerate fathers neglecting financial responsibilities toward their families. These findings highlight the urgency of employing legal mechanisms to reshape societal attitudes toward divorce. The study proposes several measures to address these issues: emphasizing shared family responsibilities between spouses, mandating premarital counseling and family support programs, explicitly outlining divorce consequences in court rulings, broadening participation in divorce trials, and strengthening regulations on the enforcement and supervision of child and spousal maintenance rights. These recommendations aim to create a more equitable and accountable legal culture, contributing to the long-term stability and well-being of families in Indonesia.